Clinicopathological characteristics and treatment outcomes of biliary neuroendocrine carcinoma: a single-center case series and literature review - Liu, Zhipeng; Yang, Faji; Hao, Yijie; Zhao, Yuan; Zhang, Shizhe; Niu, Zheyu; Wang, Xin; Sun, Liyang; Zhu, Huaqiang; Cui, Fengyun; Lu, Jun; Gao, Hengjun; et al. (Frontiers in Oncology, 2026)
ObjectiveTo investigate the clinicopathological characteristics, treatment strategies, and prognostic outcomes of biliary neuroendocrine carcinoma (Biliary NEC), and to review the relevant literature to provide further evidence for the clinical management of this rare malignancy.MethodsWe retrospectively analyzed the clinical data of nine patients who underwent surgical resection and were pathologically diagnosed with biliary NEC at Shandong Provincial Hospital between May 2012 and October 2025. Clinical manifestations, imaging findings, surgical procedures, histopathological and immunohistochemical results (Syn, CgA, CD56, Ki-67), and follow-up outcomes were collected. Overall survival (OS) was estimated using the Kaplan–Meier method. Additionally, published case reports and case series from 2020 onward were reviewed for comparison.ResultsAmong the nine patients (3 males and 6 females; median age, 65 years; range, 57–77 years), the primary tumor sites included the gallbladder (n = 4), hilar bile duct (n = 3), and distal bile duct (n = 2). The main presenting symptoms were abdominal discomfort (n = 6) and jaundice (n = 3). All tumors were poorly differentiated NECs, comprising six small-cell and two large-cell types, with Ki-67 indices ranging from 30% to 80% (median, 70%). Immunohistochemistry showed Syn (+), CgA (±), and CD56 (±), with partial expression of SSTR2. All patients underwent curative-intent resection (R0 in 8 and R1 in 1), and four received systemic chemotherapy initiated after documented tumor recurrence. The median follow-up duration was 649 days (range, 67–953 days), and the median OS was 649 days (95% CI: 85–1213 days). A review of the literature revealed that systemic chemotherapy, particularly platinum-based regimens, was associated with longer median survival (18 vs. 9 months).ConclusionsBiliary NEC is a rare and highly aggressive malignancy with nonspecific clinical manifestations, and its diagnosis relies primarily on histopathological and immunohistochemical evaluation. Surgical resection remains the cornerstone of treatment, while systemic chemotherapy may provide additional survival benefit in selected patients. A high Ki-67 index and lymph node metastasis have been consistently reported as adverse prognostic indicators in biliary neuroendocrine carcinoma, primarily based on evidence from previously published studies. Given the limited sample size of the present case series, our observations should be interpreted as descriptive rather than statistically conclusive. Future multicenter studies incorporating molecular and immunologic profiling are warranted to clarify the biological behavior of biliary NEC and to optimize individualized therapeutic strategies.